(untitled) (Ustozlar uchun, 2025)
This article provides an overview of the most important statistical measures used in corpus linguistics for quantitative analysis of language data. Modern corpus linguistics combines linguistics with statistics to study how often words, structures, and patterns occur in real communication. Statistical measures such as frequency, dispersion, log-likelihood, chi-square, Mutual Information (MI), and t-score help researchers identify meaningful linguistic patterns, collocations, and register variation.